Study of maternal and neonatal outcome in teenage pregnancy - Mundhe, Sharvari; Patil, Varsha; Saha, Divya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Teenage is a period of transition from childhood to adulthood. According to WHO, the period of teenage extends from 11-19 years. The objective of the present study was to find out the incidence and to evaluate the effect of pregnancy in teenage girls (13-19 years) and its maternal and neonatal outcome. Methods: Prospective observational cohort study, the duration from 1st January 2016 to 31st July 2017. Results: 216 teenage patients were studied; however medical termination and abortions were excluded as the study includes both maternal & neonatal outcome. 3944 pregnant patients were admitted for delivery and abortion related care. Out of this, pregnant adolescents were 216. Proportion of adolescent pregnancy was 5.47%. 170(78.7%) were booked, 32 (14.81%) were unmarried, while 50 (23.1%) were literate. Primigravida were 189 (87.5%) & multigravida was 27 (12.5%).39 (18.05%) were Anemic, Preterm labour occurred in 14 (6.5%) & PROM occurred in 41 (18.9%) patients. Preeclampsia and Eclampsia occurred in 27 (12.5%) and 14 (6.5%) respectively. There were 176(81.48%) normal vaginal deliveries.36 (16.66%) had Lower Segment Caesarean Section; commonest indication being Cephalopelvic disproportion (25%) & 4(1.85%) were instrumental deliveries 53 (24.3%) babies required admission at Neonatal Intensive care unit. Low Birth weight babies were 15 (28.3%). Conclusions: - Early ANC registration and good antenatal care with effective intrapartum & postpartum monitoring along with contraceptive advice on discharge help reduce maternal and neonatal morbidity & mortality associated with teenage pregnancy. However, it is evident that teenage pregnancy rates could be reduced by effective measures like sex education in schools, community-based programs, widespread awareness about contraception.